Regulation and Function of Axon Guidance and Adhesion Molecules During Olfactory Map Formation - Schwarting, Gerald A. (2011)
The olfactory system presents a practical model for investigating basic mechanisms involved in patterning connections between peripheral sensory neurons and central targets. Our understanding of olfactory map formation was advanced greatly by the discovery of cAMP signaling as an important determinant of glomerular positioning in the olfactory bulb. Additionally, several cell adhesion molecules have been identified recently that are proposed to regulate homotypic interactions among projecting axons. From these studies a model has emerged to partially explain the wiring of axons from widely dispersed neuron populations in the nasal cavity to relatively stereotyped glomerular positions. These advances have revitalized interest in axon guidance molecules in establishing olfactory topography, but also open new questions regarding how these patterns of guidance cues are established and function, and what other pathways, such as glycosylation, might be involved. This review summarizes the current state of this field and the important molecules that impact on cAMP-dependent mechanism in olfactory axon guidance.